Optimization of concrete composition with addition of zeolitic tuff - Markiv, T.; Huniak, O.; Sobol, Kh. (Видавництво Львівської політехніки, 2014)
In this article concrete mixture composition with the additives of zeolitic tuff and superplasticizer was optimized by the method of mathematical planning of experiment. The research reveals that use of optimal amount of zeolitic tuff results in increasing strength of concrete at later age of hardening and does not influence significantly the water absorption, porosity and freezing temperature of the liquid phase of fresh frozen concrete mixture. Методом математичного планування експерименту оптимізовано склад бетонної суміші з добавкою цеолітового туфу та суперпластифікатора. Дослідження показали, що використання оптимальної кількості цеолітових туфів призводить до зростання міцності у пізніші терміни тверднення і несуттєво впливає на водопоглинання, пористість і температуру замерзання рідкої фази свіжозамороженої бетонної суміші.
Keywords: concrete; zeolitic tuff; superplasticizer; chemical admixture; бетон; цеолітовий туф; суперпластифікатор; хімічна добавка